2019
DOI: 10.3389/fpls.2019.00629
|View full text |Cite
|
Sign up to set email alerts
|

Soil Moisture Determines Horizontal and Vertical Root Extension in the Perennial Grass Lolium perenne L. Growing in Karst Soil

Abstract: Karst regions are characterized by heterogeneous soil habitats, with shallow wide soil (SW) on hilly slopes and deep narrow soil (DN) in rocky trenches. To make full use of limited water and nutrients, plants have therefore developed a number of root extension strategies. This study investigated the effect of soil moisture on horizontal root extension in SW and vertical root extension in DN by assessing root growth responses, biomass allocation, and root distribution. A full two-way factorial blocked design of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…The morphological characteristics of choy sum roots as quantified in this study revealed that even though reduced soil water content affects plant roots, maintaining the water content in the soil throughout the growing season improves yield and plants adaptability. It is well known that root systems can change their morphological structure in response to the soil environmental conditions such as temperature and soil water content [51]. Root development in choy sum was affected by the soil moisture content in this study.…”
Section: Effect Of Water Stress On Root Morphological Traits Of Choy Summentioning
confidence: 61%
See 1 more Smart Citation
“…The morphological characteristics of choy sum roots as quantified in this study revealed that even though reduced soil water content affects plant roots, maintaining the water content in the soil throughout the growing season improves yield and plants adaptability. It is well known that root systems can change their morphological structure in response to the soil environmental conditions such as temperature and soil water content [51]. Root development in choy sum was affected by the soil moisture content in this study.…”
Section: Effect Of Water Stress On Root Morphological Traits Of Choy Summentioning
confidence: 61%
“…However, many studies have reported that crop roots tend to grow deeper into the soil when the immediate soil the root occupies is deficient in water [39,[53][54][55][56][57][58] with one study reporting that root growth of plants in water stress conditions reduced root development and may cause root damage. Chung et al and Zhang et al [51,58] reported that the drought level and root growth were inversely related if the drought occurred from the onset of planting or early growth stages. Results from this study inveterate that severe water stress limits root growth throughout the choy sum growth especially during the early and flower development stages.…”
Section: Effect Of Water Stress On Root Morphological Traits Of Choy Summentioning
confidence: 99%
“…The soil cover thickness may explain the increase in soil moisture content (Fig. 5) which has greater effect on roots extension [13] which has positive impact on potato tubers development. Mulching with about 15cm soil covering depth (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…All three species are cool‐season C 3 perennial grasses. Phalaris and Festuca are considered deep rooted (Norton et al, 2016; Volaire & Lelièvre, 2001), while Lolium exhibits a shallower, fibrous root system (Zhang et al, 2019).…”
Section: Methodsmentioning
confidence: 99%